Electrical field characteristics for rectangular patch antenna with perturbation slot at Thz range - Ismail, M. K. H. (2012)
Terahertz, THz, antennas have received much attention due to their capability to concentrate field energy and ability to support a wide range of applications such as energy collector and magnetic storage. In this paper, a rectangular patch antenna with perturbation slot is presented. The design is based on the Transmission-Line model. The dominant resonance shows good agreement at THz band with small inaccuracy of ~15 %. A single perturbation slot is introduced at the half-patch length. By having a perturbed slot, the dominant resonance moves to a higher mode. The design approach has successfully proved that the electrical field strength is highly concentrated at the perturbed slot. The studies have shown that the proposed antenna can effectively concentrate the THz field when the perturbation slot is small. Further work is focused on embedding two or three identical slots into the radiating structure in order to create more potential space to trap the electrical field.